Evaluasi Program Keluarga Harapan (PKH) dalam Mengurangi Kemiskinan di Aceh Utara - Intan Zahara; Muhammad Muhammad; Amru Alba (Asia-Pacific Journal of Public Policy, 2019)
The purpose of this research is to identify and describe the evaluation of the Family Hope Program (PKH) along with the obstacles that occur in the evaluation of reducing poverty. The approach used in this study was a descriptive qualitative method. The technique of obtaining data is attained through observation, interviews, and documentation. The results of the study determined that in Dewantara District (North Aceh), 1,929 beneficiary families received conditional social assistance and 133 families who were already prosperous. Besides, there are 8 assistants for the PKH and 1 Coordinator for Dewantara District. The conclusion is that the evaluation of the PKH has not been realized effectively, there are still very poor households that have not received assistance, inaccurate statistical data in the field are found data on the well-off people and data on the poor, children in education who do not meet the 85% attendance requirement, there are obstacles in the process of disbursing funds, changing the period of the village apparatus, beneficiary families not participating in socialization or routine meetings, as well as diverting funds to buy basic daily needs not for educational needs. It is hoped that they can find the best way so that the community can receive the assistance as expected.